A Escalada de uma Vida: A viagem atribulada de uma Professora-Estagiária em busca do Topo da Montanha - Catarina Queirós Fernandes (2022)
The following document is entitled Final Internship Report and was prepared within the scope of the Professional Internship Curricular Unit in the 2nd cycle of studies leading to the attainment of the Master's degree in Physical Education Teaching in Basic and Secondary Education. This Internship represents the beginning of a fundamental stage with regard to teacher training, and allows Intern Students, in contact with a real teaching contexto, to gain access to the complex nature of the teaching-leraning process over a school year. Thus, they should seek to apply he knowledge acquired during the 1st year of the cicle of studies in the contexto of pedagogical practice. Therefore, the document intends to present the experiences and learning lived and felt in the context of the Professional Internship, being divided into six chapters that range from personal characterization to future expectations, passing through learning, conceptions, reflective practices, teaching models and problems felt over a year of teaching in two classes, 12th and 5th grade. Accompanied by a permanente metaphor, this Report sees the Professional Internship as a troubled journey to the top of a mountain that culminates in the dream of a young Intern Student who lets vulnerability and empathy guide the way. The top of the mountain has a goal in mind that not even the falls and slips allowed it to leave the central focus: to ensure that students had the best teaching-learning process, ensuring that their experiences and sharing contributed to their individual growth not only as students, but mainly as human beings. KEYWORDS: